On combining neighbouring extremals with control parameterization - Liu, C.; Lin, Qun; Loxton, Ryan; Teo, Kok Lay (IEEE, 2015)
In this paper, we consider the neighbouring extremals for a class of optimal control problems with control constraints. We rst solve the optimal control problem using control parameterization method to obtain the optimal open-loop control and the optimal reference state. Then, a neighbouring feedback control law is derived for small state perturbations caused by changes on reference state at switching times.